Day 2 Thu, March 16, 2023 2023
DOI: 10.2118/212818-ms
|View full text |Cite
|
Sign up to set email alerts
|

CCUS and Comparison of Oil Recovery by Huff n Puff Gas Injection Using Methane, Carbon Dioxide, Hydrogen and Rich Gas in Shale Oil Reservoirs

Abstract: The objective of this paper is to compare oil recoveries by huff ‘n’ puff gas injection using methane (CH4), carbon dioxide (CO2), hydrogen (H2) and rich gas (70% CH4, 20% C3H8, plus 10% C6H14), and to advance some ideas regarding carbon capture, utilization and storage (CCUS) of CO2, and storage of hydrogen when these gases are used in huff ‘n’ puff operations. The procedure considers a real huff ‘n’ puff pilot well in the Eagle Ford shale of Texas with methane injection. Following history matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…CO 2 huff and puff technology in the United States Bakken shale reservoir, Jianghan oilfield salt shale reservoir, Changqing oilfield Jiyuan tight reservoir field test showed good effect of increasing oil production . For the experimental study of indoor CO 2 huff and puff, some scholars compared the mining effects under N 2 and CO 2 injection by carrying out shale oil huff and puff experiments with N 2 and CO 2 injection, and verified the huge potential of CO 2 huff and puff in improving shale oil recovery. Also, by studying the effects of permeability, fracture, injection pressure, miscible conditions, and soaking time on the huff and puff effect, the best injection parameters were optimized. , CO 2 has a good extraction effect on shale oil. Some scholars studied the effects of injection pressure, soaking time, and fracture number on supercritical CO 2 extraction for shale oil from shale samples in Shengli Oilfield and found that light components could be extracted easily. CO 2 also has a strong diffusion effect.…”
Section: Introductionmentioning
confidence: 95%
“…CO 2 huff and puff technology in the United States Bakken shale reservoir, Jianghan oilfield salt shale reservoir, Changqing oilfield Jiyuan tight reservoir field test showed good effect of increasing oil production . For the experimental study of indoor CO 2 huff and puff, some scholars compared the mining effects under N 2 and CO 2 injection by carrying out shale oil huff and puff experiments with N 2 and CO 2 injection, and verified the huge potential of CO 2 huff and puff in improving shale oil recovery. Also, by studying the effects of permeability, fracture, injection pressure, miscible conditions, and soaking time on the huff and puff effect, the best injection parameters were optimized. , CO 2 has a good extraction effect on shale oil. Some scholars studied the effects of injection pressure, soaking time, and fracture number on supercritical CO 2 extraction for shale oil from shale samples in Shengli Oilfield and found that light components could be extracted easily. CO 2 also has a strong diffusion effect.…”
Section: Introductionmentioning
confidence: 95%
“…Methane (CH 4 ), as a potent greenhouse gas, warrants attention because of its significant global warming effect compared to carbon dioxide (CO 2 ). Recent data shows a concerning surge in global atmospheric CH 4 levels since 2007, with a marked increase from 2014 . Concurrently, with governments increasingly focusing on CO 2 issues and the maturation of carbon capture, utilization, and storage (CCUS) technologies, breakthroughs have been achieved in practical applications like CO 2 -enhanced oil recovery (CO 2 -EOR), coal bed methane (CO 2 -ECBM), and shale gas (CO 2 -ESG). However, the high pressures required to achieve supercritical CO 2 injection states might inadvertently heighten the risk of natural gas (predominantly CH 4 ) leakages, potentially jeopardizing adjacent ecosystems and communities.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, CO 2 injection for huff-n-puff oil recovery is the most widely used method. By injecting CO 2 into the formation, the energy of the formation is replenished, and CO 2 storage and displacement of oil are achieved [52].…”
Section: Introductionmentioning
confidence: 99%